1984
DOI: 10.1099/0022-1317-65-7-1183
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus Replication: Phosphorylation of Polypeptides Synthesized in Trichoplusia ni Nuclear Polyhedrosis Virus-infected Cells

Abstract: SUMMARYA number of polypeptides synthesized specifically in Trichoplusia ni multiple nucleocapsid nuclear polyhedrosis virus (T. ni MNPV)-infected Spodopterafrugiperda cells are phosphorylated both early and late in infection. Certain non-structural proteins and the major basic internal protein are the main phosphoproteins detected in infected cells. The polyhedron protein was not phosphorylated. Many cell proteins continue to be phosphorylated throughout infection. Pulse--chase experiments have shown that som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…However, phosphorylation of pp31 appeared to lag slightly behind synthesis, because labeling with 35 S was first detected at 0 to 4 h postinfection whereas labeling with 32 P i was first detected at 4 to 8 h postinfection. Previously, it had been reported that 32 P i -labeled pp31 was detected only in the nuclear fraction (11,18), but we clearly detected phosphorylated pp31 in both the cytosolic and nuclear fractions in this study (Fig. 2B).…”
Section: Time Course Of Pp31 Synthesis and Phosphorylationsupporting
confidence: 50%
“…However, phosphorylation of pp31 appeared to lag slightly behind synthesis, because labeling with 35 S was first detected at 0 to 4 h postinfection whereas labeling with 32 P i was first detected at 4 to 8 h postinfection. Previously, it had been reported that 32 P i -labeled pp31 was detected only in the nuclear fraction (11,18), but we clearly detected phosphorylated pp31 in both the cytosolic and nuclear fractions in this study (Fig. 2B).…”
Section: Time Course Of Pp31 Synthesis and Phosphorylationsupporting
confidence: 50%
“…Phosphorylation or dephosphorylation is often associated with protein activation or inactivation, respectively. Baculovirus proteins undergo phosphorylation in infected cells (63,64), and multiple phosphoproteins were detected in BV and ODV (12,63,64). A total of 23 baculoviral proteins were identified as phosphoproteins in our study (Table 3).…”
Section: Discussionmentioning
confidence: 94%
“…Nucleocapsids were purified from detergent-treated virus particles as described by Bur|ey et al (1982). 3:p-radiolabelled CRV was produced as described by Kelly & Lescott (1984).…”
Section: Introductionmentioning
confidence: 99%